Decoy Exosomes Offer Protection Against Chemotherapy‐Induced Toxicity (Adv. Sci. 32/2022). Issue 32 (14th November 2022) - Fan, Miao; Li, Hang; Shen, Deliang; Wang, Zhaoshuo; Liu, Huifang; Zhu, Dashuai; Wang, Zhenzhen; Li, Lanya; Popowski, Kristen D.; Ou, Caiwen; Zhang, Kaihan; Zhang, Jinchao; et al.
Abstract : Chemotherapy Chemotherapy, such as doxorubicin, prolongs the life span of cancer patients but can also bring undesirable side effects, including cardiotoxicity. In article number 2203505, Jinchao Zhang, Ke Cheng, Zhenhua Li, and co‐workers employ tetrahedral DNA engineered exosomes as decoys to remove excessive doxorubicin and mitigate cardiotoxicity, without affecting the anti‐cancer effects of doxorubicin.